A toxidade do ácido ascórbico em plantas de arroz silenciadas nas APXs cloroplásticas induz estresse oxidativo não dependente da fotossíntese - Castro, Jamyla Lima Saboya de (2014)
Ascorbic acid (AA) is one of the most important antioxidants in plant protection against the oxidative stress generated by abiotic stresses. In animal cells, several works have shown that high concentrations of this acid can cause toxicity and cell death. The proposed mechanism is related to a pro-oxidant action by the reduction of Fe+3 to Fe+2 and by the action of this Fe+2 in the Fenton reaction with generation of reactive oxygen species (ROS). To the best of our knowledge, this mechanism has not been reported yet. The objective of this work was to elucidate toxicity mechanisms of high concentrations of AA in plants using rice mutants with deficiency (gene silencing) in two chloroplastic APX (stromal and thylakoidal) as model. Forty-five days old silenced plants and non-transformed (NT) were exposed to 10 mM (moderate concentration) and 50 mM (high concentration) of exogenous AA (sprayed on leaves). These concentrations were defined based on dose-dependent experiments from 0 to 50 mM using leaf segments in plates. In order to assess the protective effect (antioxidant) of the AA, plants and leaf segments were exposed to high light intensity (1000 µmol m-2 s 1) to induce photooxidative stress. AA concentrations higher than 30 mM induced oxidative stress (increase in the TBARS level) in leaf segments and this effect was enhanced by high light. In addition to the oxidative damage, these AA concentrations induced an increase in membrane damage (electrolytes leakage) and reduction in photosystem II integrity (Fv/Fm). Interestingly, the 10 and 20 mM concentrations did not mitigate the negative effects caused by the light excess. The high AA concentration (50 mM) induced leaf senescence under high light, indicated by the decrease in chlorophyll and carotenoids contents. Plants deficient in two chloroplast APX (APX7/8) displayed higher sensibility to AA toxicity, especially in combination with high light. These effects were indicated by exhibition of higher levels of TBARS (lipid peroxidation), electrolyte leakage, H2O2 and superoxide radical. Curiously, the transgenic plants under high AA concentrations did not exhibited differences for several photosynthetic parameters: CO2 assimilation rate and PSII (ΦPSII, ETR, NPQ e Fv/Fm) and PSI efficiency indicators (ΦPSI, ETR e P700), apart from the estimation of cyclic flux (CEF), compared with NT. Despite the AA toxicity have not changed the parameters of photosynthesis in APX-deficient plants, the sole presence of high light caused changes in some parameters of photochemical activity in these plants.The data set of this work shows that the excess of AA may cause toxicity in plants. The intensity of these effects is strongly enhanced by the excess of light but they are not dependent on photosynthesis. In this work, the roles of the two chloroplastic APX and/or high light on the AA toxicity still unclear, despite the deficient plants had showed increased sensibility. Apparently, the mechanism of AA toxicity in plants is similar to the proposed for animal cells.This antioxidant, when in excess, can act as a pro-oxidant stimulating Fenton reactions, inducing the accumulation of ROS and resulting oxidative stress. Further studies are needed to elucidate the role of the chloroplast APXs and high light on the toxicity of ascorbic acid in plants.